(untitled) (Plant Tissue Culture and Biotechnology, 2020)
Agrobacterium-mediated genetic transformation was carried out for Asterix (BARI Alu- 25), a popular potato (Solanum tuberosum L.) variety cultivated in Bangladesh. For Direct organogenesis of shoots the best response was noted when nodal segments and microtuber discs of Asterix along with Diamant - another popular potato variety were cultured on MS with 4.0 mg/l BAP and 1.0 mg/l IAA. MS without plant growth regulators was most effective for root induction from the excised regenerated shoots. Following optimum root development, the in vitro regenerated plantlets were successfully established in soil. Agrobacterium tumefaciens strain LBA4404/pBI121 containing GUS and nptII genes showed maximum transformation response in nodal segment with bacterial suspension having an optical density of 0.6 at 600 nm in Asterix variety. Moreover, 30 min incubation followed by 72 hrs co-cultivation was found most effective for transformation as has been determined by transient GUS histochemical assay. Transformed shoots were selected using MS with 4.0 mg/l BAP, 1.0 mg/l IAA, 0.5 mg/l GA3, 300 mg/l carbenicillin and 200 mg/l kanamycin. Stable integration of GUS and nptII genes were confirmed by PCR analysis using the genomic DNA isolated from transformed shoots. Plant Tissue Cult. & Biotech. 30(1): 149-160, 2020 (June)